Educators’ Voices Of Culturally Responsive Pedagogy In Elt Context: Revealing The Dominant Characteristics And Praxis - Herda, Rozanah Katrina; Robiasih, Hasti; Kozuka, Yoshitaka; Margana, Margana (Wahana Pendidikan, 2025)
When teaching English in a multicultural setting, culturally responsive pedagogy (CRP) becomes even more important. It promotes diversity by recognizing the impact of students' different backgrounds and experiences on their identities. Teachers can increase student engagement, foster critical thinking, and improve language acquisition by incorporating culturally relevant materials and teaching strategies. This method respects students' cultural backgrounds and enhances their ability to understand and empathize with individuals from diverse backgrounds. The purposes of this mixed-method study with an explanatory design were to 1) find out what English language teachers think are the most important aspects of CRP and 2) find out how they use CRP to keep students interested. The participants (N = 95) are majoring in English from elementary, secondary, and higher education levels. The researchers used an online questionnaire and a semi-structured interview to gather the data from respondents. The researchers analyzed the questionnaire using the adjectival rating of a four-point Likert Scale and analyzed the interview using the verbatim technique. The findings revealed that the dominant key characteristics of CRP were care and empathy. Therefore, the interview results indicated that practicing CRP successfully boosted student engagement since their involvement and motivation appeared as well since teachers were 1) using relevant contexts and examples, 2) incorporating multicultural perspectives, 3) encouraging student-driven material selection, and 4) making personalization of content.